Bitcoin: a future currency? / Dr. Muhammad Zarunnaim Wahab - Wahab, Muhammad Zarunnaim (Universiti Teknologi MARA, Kedah, 2022)
The world today depends heavily on the technology and people use it in their whole aspect of life. Over the years, technology has consistently revolutionized and has created many amazing tools and resources as well as putting useful information at our fingertips. Currently, the Fourth Industrial Revolution (IR 4.0) has begun to show significant effects and changes in our daily life. IR 4.0 aims to use artificial intelligence (AI) and the Internet of Things (IoT) as the main platform to accelerate the effort. This will see new technologies such as robotics, big data, computers and automation will take over and dominate the future work. IR 4.0 also gives a significant impact to banking and finance sectors. One of the most significant impacts in financial transactions is the use of financial technology (FinTech) and digital currency, or also known as ‘cryptocurrency’. One of the famous cryptocurrencies is known as ‘bitcoin’. In short, bitcoin was founded by Satoshi Nakamoto (believed to be a pseudonym) who published an article entitled 'Bitcoin- A Peer-To-Peer Electronic Cash System' in November 2008 that explained how the digital currency transaction took place.